Detection of Candida albicans Fungus in Urine of Women with Vaginal Discharge by PCR Method - Pujianti, Yunita Putri; Qurrohman, Muhammad Taufiq (Jurnal Biologi Tropis, 2025)
Candida albicans is a type of fungus responsible for pathological vaginal discharge and the most pathogenic among other Candida fungal species. The development of PCR-based molecular techniques used for identification and characterization of fungi by isolating DNA from the quality and quantity to analyze through PCR-based applications. The purpose of this study is to determine the presence of Candida albicans fungi in urine isolate samples of women who experience vaginal discharge. The research method used was descriptive. The samples used were 10 female urine samples that experienced vaginal discharge in students of the Bachelor of Applied Medical Laboratory Technology study program of STIKES Nasional class of 2023. Based on the results of research it can be concluded that the Candida albicans fungus can be detected in the ITS1 region with a product length of 219bp and the ITS2 region with a product length of 338bp using the conventional PCR method. The concluded of this study is Candida albicans fungus can be detect in the ITS1 region with a product length of 219bp and the ITS2 region with a product length of 338bp using the conventional PCR method.